(untitled) (Itinera, 2019)
This special issue gathers some of the papers presented on occasion of the international conference Women Representing Women in Theatre, held at the University of Milan on 20th-21th May 2019. With no pretence of being exhaustive and adopting a diachronic perspective, the following contributions examine women’s theatre in Italy in the last five decades—from the educational theatre of the early 1900s to the feminist dramaturgy and from the literary rendition of intergenerational conflicts to contemporary rewritings of the patriarchal script. Their differences notwithstanding, all the dramaturgical forms examined in this issue share a marked concern for existing (theatrical and social) conventions and the willingness for their authors to reclaim new form of self-representation — indeed, a stage of their own.